Red Hat certified system administrator (RHCSA) and Red Hat certified engineer (RHCE). - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2019)
Overview This title includes Red Hat Certified System Administrator (RHCSA) Complete Video Course, 3/e and Red Hat Certified Engineer (RHCE) EX294 Complete Video Course: Red Hat Ansible Automation, 3/e Prerequisites Know your way around a computer Basic IT knowledge No experience of Linux is necessary, but it is helpful Description Welcome to the Red Hat Certified System Administrator (RHCSA) and Red Hat Certified Engineer (RHCE) Library . This title includes coverage of both the RHCSA and RHCE exams, so it is your one-stop shop for your Red Hat certification needs. The Red Hat Certified System Administrator (RHCSA) Complete Vide Course, 3rd edition is all new and fully updated for RHEL 8. This course is designed to teach you everything you need to know to pass the RHCSA exam. Every objective in the exam is discussed, along with in-depth lessons on complex topics, so they are not confusing. Each lesson ends with a lab, so you can dive into your own projects and see Red Hat in action; many of these labs mimic scenarios you might find on the exam, so you get the experience you need to practice for the exam. These labs also include video solutions, so you can also see in real-time how to work through the problems and figure out the best methods for working through each scenario. Red Hat Certified Engineer (RHCE) EX294 Complete Video Course, Third Edition: Red Hat Ansible Automation is all new and fully updated. This 10-hour video course provides a solid understanding of all the topics required to pass the RHCE exam and includes live demos, exam question walk-throughs, and dynamic lightboard teaching. The student learns how to perform common automation tasks using Ansible, as well as how to use common Ansible components to automate the management of a Linux environment. About the Instructor Sander van Vugt has been teaching Linux classes since 1995 and has written more than 60 books about different Linux-related topics. Sander is a Red Hat Certified Instructor and has deep knowledge and understanding of Red Hat Enterprise Linux, including the upcoming Red Hat Enterprise Linux 7. He has been teaching Linux since 1994, and as a Red Hat Certified Examiner, he is authorized to proctor different Red Hat exams. He is also a regular speaker on major Linux conferences all over the world. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Prentice Hall, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.